Adverse Neonatal Outcomes in the Setting of Inflammatory Bowel Disease [A241]. (May 2022) - Chaiken, Sarina; Ghafari-Saravi, Afsoon; Packer, Claire; Garg, Bharti; Caughey, Aaron
Abstract : INTRODUCTION: To examine neonatal outcomes among pregnant patients with inflammatory bowel disease (IBD). METHODS: A retrospective cohort study using linked vital statistics and hospital discharge data from California (2007–2011). We included singleton, non-anomalous pregnancies, using chi-square tests to compare demographics and outcomes of intrauterine fetal demise (IUFD), infant death, NICU admission >24 hours, Apgar score <7 at 5 minutes, and small for gestational age. Multivariate logistic regressions controlled for maternal age, race/ethnicity, education, and insurance. RESULTS: The cohort included 1, 559 (0.06%) individuals with IBD. Compared to those without IBD, IBD patients were more likely to be White, older, highly educated, on private insurance, and with normal BMI. Pregnancies of patients with IBD were more likely to result in NICU admission ( P <.001), small for gestational age neonates ( P =.004), or congenital anomaly ( P =.049), but not IUFD ( P =.105), infant death ( P =.753), Apgar score <7 ( P =.261), macrosomia ( P =.094), or birth injury ( P =.262). On multivariate regression, IBD neonates were more likely to require NICU admission (aOR, 1.71; 95% CI, 1.48–1.98) or be small for gestational age (aOR, 1.55; 95% CI, 1.32–1.83), and less likely to have macrosomia (aOR, 0.75; 95% CI, 0.62–0.90). CONCLUSION: IBD neonates were more likely to require NICU admission and be small for gestational age, but less likely to have macrosomia. When adjusting for characteristics of IBD patients, IUFD, infant death, poor Apgar scores, congenital anomaly, and birth injury were not more likely. This study is limited by the small incidence of some outcomes. Further work should elucidate how IBD is related to these adverse neonatal outcomes.